A review of therapeutic exercise strategies for prostate cancer and benign prostate hyperplasia - Jin Hwan Yoon (Korea Institute of Sport Science, 2020)
Purpose Prostate problems, such as prostate cancer, and benign prostate hyperplasia have been recognized as problems largely related to androgens and genetic factors. They affect a large fraction of the elderly population, contributing significantly to morbidity and mortality. Therefore, the purpose of this review paper was to investigate a therapeutic strategies for prostate cancer and benign prostate hyperplasia. Methods In order to determine the therapeutic exercise strategies for prostate cancer and benign prostate hyperplasia, previous literature was reviewed with MEDLINE, PubMed, and Scopus databases. Results Prostate cancer and its associated treatments can cause significant and lasting morbidities, such as cardiovascular and sexual dysfunctions. Various interventions have attempted to prevent or mitigate these dysfunctions. This review summarizes the available evidence concerning the effects of exercise training on male sexual health in the cancer prevalent population. Smoking cessation, regular exercise, and maintaining healthy weight are important public health targets for intervention. Importantly, several lifestyle modifications may lower the risk of developing more aggressive cancer or offer survival benefits to prostate cancer patients. Conclusions In this review article, physical exercise training can increase apoptosis markers in the prostate, suggesting exercise training as a potential novel therapeutic strategies for treating prostate cancer and benign prostate hyperplasia. Future studies in more advanced and varied prostate cancer populations are required to ascertain the duration, intensity and frequency of exercise that optimizes the effects of exercise training on prostate cancer and benign prostate hyperplasia.